PEMERINGKATAN KOPERASI DALAM KONTEKS PEMBERDAYAAN KOPERASI - Prihatini, Dewi (BISMA: Jurnal Bisnis dan Manajemen, 2011)
This paper provides an overview of the recent development incooperative empowerment policy in Indonesia. Objectically, cooperatives need to be empowered as an engine for improving social welfare, at the same time to force poverty alleviation. After explaining the growing awareness of the importance of cooperative, the paper discusses the current system ofcooperative classification and highlights its aims, criteria, indicators, and benefits. In the case of classifying cooperatives in Situbondo District, the result shows that 11 cooperatives classified as qualified, 51 cooperatives categorized as fairly qualified, and 8 cooperatives indified as less qualified cooperatives.